Pengaruh Green Finance, Nilai Perusahaan, Kinerja Lingkungan Terhadap Kinerja Keuangan di Sektor Perusahaan Indonesia - Putri Camelia (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This study aims to analyze the effect of green finance, firm value, and environmental performance on the financial performance of consumer staple goods sector companies in Indonesia. A quantitative approach is used with descriptive and verification research types, as well as purposive sampling techniques based on financial report data, annual, and sustainability for the 2020-2022 period. The results showed: (1) Green finance has a negative and insignificant effect on firm value; (2) Green finance has a positive but insignificant effect on financial performance; (3) Environmental performance has a positive and significant effect on financial performance; and (4) Financial performance has a positive and significant effect on firm value. The research model explains 94% of the variation in financial performance (Adjusted R² = 0.910). These findings confirm the importance of environmental commitment in improving firm performance and value, although green finance has not shown a significant impact in the short term.